DIDACTIC PRINCIPLES AND RULES OF EDUCATION (American Journal of Interdisciplinary Research and Development, 2024)
Education plays a decisive role in the formation of intellectual, social and emotional development of a person. To ensure optimal educational results, teachers use various didactic principles and rules that guide the teaching and learning process. This article examines the main didactic principles and rules of education, provides insight into their importance and practical application. By effectively understanding and implementing these principles and rules, educators can create an engaging and effective learning environment that promotes knowledge acquisition, critical thinking, and lifelong learning.